The Development of Vocational Interest Instrumen for Career Exploration of Junior High Scholl Students - Artosandi, Yudhi Satria Restu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Compulsory education has been implemented around the world despite of the variety of law and objectives. It is presumed that students’ career path can be preferred since they are engaged in this level of education, particularly in junior high school. In fact, most of students at this level of education undergo serious obstacle in exploring their preference. A few instruments or tools are actually available and relevant which can help the students in junior high school to make decision on their next education. It is so impotant to design vocational interest instruments that can provide data of counceling process for education consultation in general and junior high school in particular. Holland Theory is a pioneer in assessing the environments of colleges and universities and their influence on students. It has been a central development of knowledge on nonacademic accomplishments. This study aimed to establish a vocational interest instrument based on Holland Theory for junior high school students. It involved junior high schools students and vocational students of Surakarta as the respondent. Structural Equation Modelling (SEM) was used to identify the validity and reliability of this instrument. The yield showed the relevance of Holland Theory with empirical evidence which indicated its suitability to design vocational insterest instrument. Therefore, the instrument developed in this study is valid and reliable to be applied and it is capable in providing recomendation for the next specified education.